Heads of Science & Technology Libraries Discussion Group, ALA Midwinter January 14, 2001 - Laura Lane; Donald G. Frank (Issues in Science and Technology Librarianship, 2001)
This article reports on the Heads of Science & Technology Libraries Discussion Group meeting at ALA Midwinter, January 14, 2001.